Streptomyces-derived quorum-sensing systems engineered for adjustable transgene expression in mammalian cells and mice - Weber, Wilfried (Oxford University Press, 2003)
Prokaryotic transcriptional regulatory elements have been adopted for controlled expression of cloned genes in mammalian cells and animals, the cornerstone for gene-function correlations, drug discovery, biopharmaceutical manufacturing as well as advanced gene therapy and tissue engineering. Many prokaryotes have evolved specific molecular communication systems known as quorum-sensing to coordinate population-wide responses to physiological and/or physicochemical signals. A generic bacterial quorum-sensing system is based on a diffusible signal molecule that prevents binding of a repressor to corresponding operator sites thus resulting in derepression of a target regulon. In Streptomyces, a family of butyrolactones and their corresponding receptor proteins, serve as quorum-sensing systems that control morphological development and antibiotic biosynthesis. Fusion of the Streptomyces coelicolor quorum-sensing receptor (ScbR) to a eukaryotic transactivation domain (VP16) created a mammalian transactivator (SCA) which binds and adjusts transcription from chimeric promoters containing an SCA-specific operator module (P(SPA)). Expression of erythropoietin or the human secreted alkaline phosphatase (SEAP) by this quorum-sensor-regulated gene expression system (QuoRex) could be fine-tuned by non-toxic butyrolactones in a variety of mammalian cells including human primary and mouse embryonic stem cells. Following intraperitoneal implantation of microencapsulated Chinese hamster ovary cells transgenic for QuoRex-controlled SEAP expression into mice, the serum levels of this model glycoprotein could be adjusted to desired concentrations using different butyrolactone dosing regimes.